Synthesis, Characterization and Biological Evaluation of Some Novel Schiff’S Bases Derived from Vanillin - Khudheyer J. Kadhim (Journal of Global Pharma Technology, 2017)
Many drugs contain primary amino group can be utilized for synthesizing Schiff’s basses with different uses. A series of Schiff’s bases ( Z1 - Z5 ) have been synthesized using  (vanillin) and3,4 diaminopyridine ,procaine , Met form in , 2-arsanilic acid and RhodamineZ1 and Z2 were synthesized using acidic catalyst while basic catalyst has been used in the synthesis of Z3- Z5 .The characterization was performed using elemental analysis , FT-IR and proton NMR spectroscopes . The prepared compounds were biologically evaluated against gram positive and gram negative bacteria. The results showed excellent to moderate anti-bacterial activity.Keywords: Vanillin, Schiff’s bases, Met form in, Condensation reaction, Anti-bacterial activity, Disk diffusion method.